Dampak Pergantian Kurikulum tehadap Self-Efficacy Guru dalam Pembelajaran - M Ruhul; Hamimi, Lia (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to analyze the impact of curriculum changes on teacher self-efficacy in implementing in-depth learning at SMAN 6 Aceh Barat Daya. The method used is qualitative research with a descriptive design. The research subjects were selected using a purposive sampling technique, namely teachers who have participated in in-depth learning socialization and training. Data collection techniques were carried out through observation, interviews, and documentation, then analyzed interactively through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of in-depth learning based on the principles of meaningful, mindful, and joyful has been attempted by teachers but has not been optimal due to limited teaching aids and student concentration in adapting from the lecture method. The level of teacher self-efficacy also shows variations, namely adaptive-collaborative, intermediate influenced by student conditions, and skepticism towards repeated changes in curriculum policies. The conclusion of this study shows that curriculum changes have an impact on the process of adapting teacher self-efficacy in implementing in-depth learning. The success of curriculum implementation is not only determined by teachers' pedagogical competence, but is also influenced by support for collaboration between teachers, ongoing training, and the availability of school facilities and infrastructure.   Keywords: Curriculum, Deep Learning, Teacher's Self-Efficacy